On point-local deformations of minimal extensions of non-serial Dynkin diagrams - Bondarenko, V. M.; Chervyakov, I. V.; Pereguda, Yu. M. (Збірник Праць Інституту математики НАН України, 2015)
In this paper we study point-local deformations of Tits quadratic forms of finite graphs. We describe all P-limiting numbers of minimal extensions of non-serial Dynkin dyagrams in the case when these extensions are neither usual neither extended Dynkin diagrams.